Renewable energy to improve energy situation in African island states. (May 2018) - Surroop, Dinesh; Raghoo, Pravesh
Abstract: The energy situation of the African island states which include Cape Verde, São Tomé and Príncipe, Comoros, Guinea-Bissau, Madagascar, Mauritius and Seychelles are overwhelmingly dependent on fossil fuels with paradoxically high potential of renewable energy which are sparsely developed. This paper lay emphasis on the present electricity situation in these countries and highlights the potential of renewable energy resources on their territories. Among Africa islands, demographic and economic features are dissimilar and their power sector is complex by unique challenges. It is seen that there is a critical lack of electricity in Guinea-Bissau and Madagascar, which are 21% and 13% respectively, due to political instability and high spending on diesel. Moreover, the electricity consumption per capita is alarming in Guinea-Bissau, Comoros and Madagascar where it is below the average consumption for low income countries. Sustainable energy supply can be achieved by renewable energy sources, however, not all renewable resources are technically and economically feasible for development in these countries, for example wind in Comoros and hydro in Mauritius have little potential – which this paper elaborated further. Based on these analysis, a roadmap was developed, on to how to address some of the energy issues in these countries and accelerate the uptake of renewable energy. Through energy governance reform, political decision makers can drive change within their government, especially when a reform entails opening market opportunities and stimulating private participation and exerting pressure on existing government agencies to work efficiently.